Exploring the Perspectives of Croatian Librarians on Citizen Science - Dolores Mumelaš; Antonija Filipeti (Liber Quarterly: The Journal of European Research Libraries)
This study explores the significance of librarian education on implementing citizen science initiatives in their own operations. The first part of the study is dedicated to reviewing global practices in certified librarian education on citizen science, highlighting the growing recognition of its importance within library education and practice. Drawing on examples from various countries, it emphasizes the importance of continuous education and training for librarians to effectively support citizen science initiatives within their communities. The second and central part of the study explores the experiences and insights gathered from a certified webinar titled Citizen Science in Libraries, organized by the Training Centre for Continuing Education of Librarians in Croatia (CSSU) from the National and University Library in Zagreb (NUL). A research study was conducted among the webinar participants to investigate their opinions regarding the content and effectiveness of the webinar and their attitudes towards the implementation of citizen science in libraries. A survey was conducted using an online questionnaire with the participation of 332 webinar attendees, which represents 69.31% of the total number of participants. The main conclusions highlight the positive attitudes of librarians towards the webinar and potential strategies for enhancing library participation in citizen science. The importance of continuous education and collaboration is emphasized to maximize the potential of libraries in promoting citizen science and raising awareness of its importance in the community. The findings can serve as an incentive for other libraries to implement similar educational programs and encourage librarians to participate in such initiatives. Additionally, the proposed research model can be valuable for libraries already conducting educational activities, as they can translate and incorporate it as an integral part of their program.